2008
DOI: 10.1063/1.2975179
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of nanodefect properties in optical coatings by coupling measured and simulated laser damage statistics

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 40 publications
0
37
0
Order By: Relevance
“…5 Many experimental facts have shown that absorbing nanometer-sized inclusions are responsible for the initiation of the damage process: an increase of the damage thresholds with purification of subsurface of fused silica; 6,7 a spatial variation of the damage threshold on the surface or in bulk of optical substrates; 8,9 and a dependence of the damage threshold on the irradiation spot-size and wavelength. 10,11 However, in most cases, the impurities are not identified by modern optical techniques since they are nanoscale size and are distributed at low concentration. 12 It is obvious that the inclusion-initiated damage has a statistical character because of the spatial distribution of inclusions in a sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Many experimental facts have shown that absorbing nanometer-sized inclusions are responsible for the initiation of the damage process: an increase of the damage thresholds with purification of subsurface of fused silica; 6,7 a spatial variation of the damage threshold on the surface or in bulk of optical substrates; 8,9 and a dependence of the damage threshold on the irradiation spot-size and wavelength. 10,11 However, in most cases, the impurities are not identified by modern optical techniques since they are nanoscale size and are distributed at low concentration. 12 It is obvious that the inclusion-initiated damage has a statistical character because of the spatial distribution of inclusions in a sample.…”
Section: Introductionmentioning
confidence: 99%
“…12 It is obvious that the inclusion-initiated damage has a statistical character because of the spatial distribution of inclusions in a sample. 10 The theoretical studies of inclusion-initiated damage were based on the resolution of Fourier equation. [13][14][15][16] However, these models have not been substantiated enough to explain the statistical character in experiments.…”
Section: Introductionmentioning
confidence: 99%
“…A useful method to obtain information on the damaging defects is to study the laser damage statistics: defect statistical model. According to this statistical model, the probability of damage P (F) is then the probability of the presence of a defect that receives more energy density than its critical fluence T. This probability can classically be expressed as [11][12][13]:…”
Section: Discussionmentioning
confidence: 99%
“…The large variations in the thermal parameters of the inclusion only weakly affect temperature evolution in the case of an absorbing inclusion driven mechanism [23]. Thus, the thermal properties of the surrounding matrix are of critical importance for the temperature rise [15], so the calculation only considers the dependence of thermal properties of the host material on the temperature. In this manuscript, considering the real temporal shape of the laser pulse by fitting a measured Gaussian temporal profile, we refined previous model [20][21][22] to calculate the particle temperature.…”
Section: Temperature and Thermal Stress Model Of Absorbing Inclusionmentioning
confidence: 99%
“…These inclusions can absorb laser energy significantly, raising the temperature around the inclusions high enough to cause damage [14]. A statistical trend has been observed in damage tests due to size distributions [15][16][17][18][19] (Dirac, power law, Gaussian law) of the inclusions. The damage density and damage probability dependend on laser parameters (fluence, pulse length, spot size, or wavelength) and this has been observed in the experiments [20][21][22].…”
mentioning
confidence: 99%